PENGARUH KECERDASAN EMOTIONAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI AKUNTANSI SMK 2 SITUBONDO SEMESTER GENAP TAHUN AJARAN 2017-2018 - Ahmad Hafas Rasyidi; siti aisyah (STKIP PGRI SITUBONDO, 2017)
The rapid development of technological science and the flow of globalization have a lot of competition in the field of education. Education is always the main concern in order to advance the lives of generations in line with the guidance of the community. The learning process in school is a complex and comprehensive process. Many people argue that to achieve high achievement in learning, a student must have a high Intelligence Quotient (IQ), because Intelligence Quotient (IQ) is a potential provision that will facilitate learning and in turn will produce optimal learning achievement Intellectual intelligence (IQ) ) only contributed 20% to success, while 80% was contributed by strength factors including emotional intelligence or Emotional Quotient (EQ), Aimed to determine the effect of Emotional Intelligence on Student Learning Outcomes in Economics Subjects Class XI Accounting SMK 2 Situbondo even semester 2017 Academic Year -2018. In testing the hypothesis there is a low influence between emotional intelligence on learning outcomes. Next, prove F hypothesis, the hypothesis will be proven if F-count is greater than F-table with a significant level of 5%. Large F-count is 10.381 while F-table is 3.1154 at N = 80, meaning that F-count is greater than F-table so it is said that there is a significant influence between emotional intelligence on learning outcomes. From the calculation of the 20 item questionnaire that has been validated. Where db = n - k - 1 = 78 with respondents 80 students, and the Ttable value seen from column db is 0.224 so if Thitung> T table then the questionnaire will be valid. After all valid questions, the next step is to record the questionnaire question, it has known reliable data of 0, 685> 0.60 and reliable 100%. The results of research conducted by researchers who use simple correlations to determine the relationship between variables is that it can get a value of 0.3428 when consulted with the empirical table that there is a low relationship between the variables of emotional intelligence on learning outcomes. To determine the effect between the variables of emotional intelligence on learning outcomes with the regression equation is = a + bx = 68,468 + 0,2194x, thus the coefficient of determination of variance is 0,3428 which means that emotional intelligence has a contribution to the learning outcomes of class XI of SMK Accounting N 2 2017/2018 Academic Year is 11.751% and the remaining 88.294% is influenced by other variables not examined.